Waste cooking oil transesterification: influence of impeller type, temperature, speed and bottom clearance on FAME yield - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; Jameel, Ahmed Tariq (Academic Journals, 2011)
Waste cooking oil (WCO) provides an alternative source of raw material for biodiesel production. The reaction is both kinetics and mass transfer limited. Industrial use of current laboratory result suffer from dimensional non-compatibility because of the difference in the production environment especially as different impeller result in different flow characteristic during chemical reaction. In this work the effect of impeller type on fatty acid methyl ester (FAME) production from WCO was studied. At an alcohol oil mole ratio of 6:1 and 1% catalyst (oil weight), the Taguchi method was used for the experimental design of the transesterification in a 2 L stirred reactor using Rushton and elephant ear impellers. An optimum yield FAME at 70°C, 650 rpm impeller speed and 30 mm impeller bottom clearance (IBC) for Rushton impeller and 70°C, 700 rpm impeller speed and 25 mm IBC for an elephant ear impeller was obtained between 89 to 94%. IBC and speed were observed to have the most significant effect on yield using the signal to noise (S/N) ratio for Rushton and elephant ear impeller. Peak yield time between 5 to 30 min was observed. Correlation between FAME yield, peak time and temperature was high (0.968). The optimum reactor setting was at temperature 70°C, impeller speed of 650 rpm and IBC of 30 mm for Rushton (unbaffled reactor) and temperature 70°C, impeller speed of 700 rpm and IBC of 25 mm for elephant ear (baffled reactor). Physical configuration affected FAME yield/time in this work.